2011
DOI: 10.1530/joe-11-0181
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone enhances estradiol's cardioprotection in ovariectomized rats

Abstract: After menopause, the development of cardiovascular disease (CVD) is due not only to estrogen decline but also to androgen decline. This study examined the effects of either estradiol (E 2 ) or testosterone replacement alone or E 2 -testosterone combination on isolated myocytes in ovariectomized (Ovx) rats subjected to ischemia/reperfusion (I/R). Furthermore, we determined whether the effects are associated with b 2 -adrenoceptor (b 2 -AR). Five groups of adult female Sprague-Dawley rats were used: Sham operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…The dose of testosterone used for hormonal treatments in postmenopausal women has been widely discussed. Studies have described that low doses (150 g/day) of testosterone can contribute to the cardioprotection in OVX rats by E 2 (29). Another group has described that 300 g of testosterone twice/week improves insulin sensitivity and muscle strength in elderly women with chronic heart failure (25).…”
Section: Discussionmentioning
confidence: 99%
“…The dose of testosterone used for hormonal treatments in postmenopausal women has been widely discussed. Studies have described that low doses (150 g/day) of testosterone can contribute to the cardioprotection in OVX rats by E 2 (29). Another group has described that 300 g of testosterone twice/week improves insulin sensitivity and muscle strength in elderly women with chronic heart failure (25).…”
Section: Discussionmentioning
confidence: 99%
“…Myocytes contraction was measured as previously described by our laboratory (Jiang and others ; Liu and others ). Briefly, myocytes were superfused with KH solution.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent work, Liu et al . demonstrated that the addition of a physiological dose of testosterone to oestrogen therapy enhances the cardio‐protection of E2 in OVX rat cardiomyocytes subjected to ischaemia/reperfusion. Combined E2 and testosterone supplementation reduced myocardial injury, increased viability, and improved contractile function through the activation of a common signalling pathway: PI3K–AKT via beta2‐AR .…”
Section: Androgenmentioning
confidence: 99%